Feedback controlled piezo-motor microdrive for accurate electrode positioning in chronic single unit recording in behaving mice - Yang, Sungwook; Cho, Jeiwon; Lee, Semin; Park, Kitae; Kim, Jinseok; Huh, Yeowool; Yoon, Eui-Sung; Shin, Hee-Sup (ELSEVIER SCIENCE BV, 2011)
The microdrive is one of the most essential tools for extracellular, single-unit recordings in freely behaving animals to detect and isolate the single-unit activities from brain regions of interest. Due to the increasing number of neuroscience research projects using genetically engineered mice, the demand for effective recording devices in freely moving mice is also increasing. Although manually and automatically operated microdrive devices are available, they are limited in terms of size, weight, accuracy, manipulability, and convenience for single-unit recording in mice. The present study proposed a novel microdrive that employs a small, lightweight piezo-motor and a magnetoresistive (MR) sensor with a closed-loop position feedback control system. The total weight of the device is 1.82 g, which is perfectly suitable for application to mice. Most importantly, the proposed microdrive is capable of monitoring and adjusting electrode movement on-line by integrating a closed-loop feedback control system, which enhances the accuracy of micro-advancement of the electrode by utilizing position feedback. The performance of this newly developed microdrive was extensively evaluated for both mechanical and physiological concerns at both free-loading and various-loading conditions, including agarose gel matrix and then the hippocampus and thalamus of mice. In summary, this proposed microdrive can enhance the quality of recording single unit activities in freely moving mice in terms of the size and weight of the device, the convenience and accuracy of manipulation, and, most of all, in isolating single neurons and recording stability by providing accurate positioning of an electrode. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: FREELY MOVING RATS; ANIMALS; DESIGN; SYSTEM; ARRAY